Cross-Cultural Management - Velo, Veronica (Business Expert Press, 2011)
Ebook from IG Library ; The book offers an introduction to cross cultural management through an exploration of the major theories that have been developed in the fields of business anthropology and international management. An introduction to the concept of culture will be followed in subsequent chapters by the comparative description of different typologies which will be used to explain various expected behaviours in intercultural business settings. This will be followed by an introduction of the fundamental issues in cross-cultural management: what is culture, how can we describe it, to what extent is it important in international business?